Survival, and Growth Response of Douglas-Fir Trees to Increasing Levels of Bole, Root, and Crown Damage. Issue 2 (21st September 2018) - Jones, Dryw A; Harrington, Constance A; Marshall, David
Abstract: We applied a range of bole and root damage treatments to young Douglas-fir ( Pseudotsuga menziesii [Mirb.] Franco) trees. Significant natural damage occurred to tree crowns over the course of the 10-year study allowing for an analysis of how damage severity to tree boles, tree roots, and tree tops impacts growth and cumulative survival of trees. Tree bole damage severity, measured by percent bole circumference removed, exponentially reduced cumulative survival across the study period, whereas damage to tree roots had no significant impact on survival. Bole damage had different impacts on survival depending on the relative size of trees that were damaged. At higher levels of bole damage, trees with larger relative diameters had accelerated mortality rates compared with trees with smaller relative diameters. Tree crown height loss averaged at the treatment within stand level reduced the impacts of bole damage on tree cumulative survival response. Increasing bole, root, and tree crown damage severity led to reductions in estimated maximum diameter and height. Bole damage and damage to tree crowns hastened the decline of diameter growth rates and delayed the decline of height growth rates.